Wanprestasi Dalam Perjanjian Jasa di Shoes and Care Ditinjau Dari Sudut Pandang Hukum Perjanjian - Muhammad Syafiq Prasetyo Nugroho; Anjar Sri Ciptorukmi Nugraheni (Lembaga Pengembangan Kinerja Dosen, 2024)
This study examines the position of notes used in transactions at Shoes and Care along with the forms of breach of contract that often occur in Shoes and Care based on a review of the law of the agreement. The research also analyzes appropriate dispute resolution alternatives to be applied with a review of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. This type of research is a field study to obtain primary data along with a literature study to obtain secondary data analyzed with interactive analysis techniques. The result of this research is the position of the memorandum in the agreement made by the consumer with Shoes and Care as a draft agreement containing several clauses agreed between the consumer and Shoes and Care orally. Often the engagement/achievements in the agreement are not fulfilled which is referred to as a state of breach of contract. The forms of breach of contract that occur can be in the form of achievements that are not carried out, achievements are not carried out in accordance with the agreed time, and achievements are not carried out properly. Breach of contract that occur can then be resolved through negotiation as an alternative to effective and efficient dispute resolution.